Effectiveness of the incredible years parenting program for children with behavioral problems: an experience in a developing country during a pandemic - Masiran, Ruziana; Ibrahim, Normala; Awang, Hamidin; Lim, Poh Ying; Chan, Tze Lin; Narayanasamy, Sankari Ganesh (Elsevier, 2022)
Although parenting programs have been supported as an effective family-based intervention for children’s behavioral problems, they are underutilized in developing countries. This randomized controlled study aims to determine the effectiveness of the Incredible Years parenting program (IYPP) in improving behavioral problems in children, parenting stress, and parental mental health. Seventy mother–child dyads from three tertiary hospitals in Malaysia were divided into the IYPP and waitlist control groups. Weekly parent training sessions were adjusted during the pandemic period. Child’s total difficulty scores of the Strength and Difficulty Questionnaire (SDQ-TDS), Parental Stress Scale (PSS) scores, and parental DASS-21 scores were measured at pre- and post-intervention, and follow-up, and analyzed using generalized estimating equation (GEE). Compared to the control group at baseline, the intervention group showed a 4.2- and a 3.5-point significantly lower SDQ-TDS at 2 weeks post-intervention and 3 months follow-up, respectively (B = -4.20, 95 % CI: −6.68, −1.72, p = 0.001; B = -3.51, 95 % CI:-6.37, −0.66, p = 0.016), a 5.0-point significantly lower PSS at 3 months follow-up (B = -5.03, 95 % CI: −9.16, −0.90, p = 0.017), and a 4.1-point significantly lower general stress scores at 2 weeks post-intervention (B = -4.06, 95 % CI: −7.20, −0.92, p = 0.011). Effect sizes were small (ds = 0.28–0.40). There was no significant intervention effect on maternal anxiety and depression scores. The modified parenting program was effective in improving children’s behavior, parenting stress, and general stress among mothers of children aged 6–12 years presented with borderline and abnormal levels of behavioral problems, with sustained effects demonstrated for child behavior. However, the interpretation of these findings requires careful consideration of potential pandemic-instigated challenges and implications.